Reseña/Review (Moreno-Caballud, Luis, "Cultures of anyone. Studies on cultural democratization in the Spanish neoliberal crisis", Trad. Linda Grabner, Liverpool: Liverpool University Press, ISBN: 9781781381939, 288 págs., 2015) - Prádanos, Luis I (Teknokultura. Revista de Cultura Digital y Movimientos Sociales, 2015)
Reseña/Review (Moreno-Caballud, Luis, "Cultures of anyone. Studies on cultural democratization in the Spanish neoliberal crisis", Trad. Linda Grabner, Liverpool: Liverpool University Press, ISBN: 9781781381939, 288 págs., 2015)